Burnside Mission Church, Bathurst Inlet, NU -- photograph - Seale, Linda N. (2001)
Burnside Mission Church at Bathurst Inlet, Nunavut : in use 1930s-1940s. Now part of Bathurst Inlet Lodge. Photograph taken June 2001